2011
DOI: 10.1007/s11249-011-9849-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact Resistance and Device Lifetime Measurements of Au-RuO2-Based RF MEMS Exposed to Hydrocarbons in Vacuum and Nitrogen Environments

Abstract: Electrical Contact Resistance (ECR) measurements are reported for RF micro-electromechanical switches with Au-RuO 2 contacts, situated within an ultrahigh vacuum system equipped with in situ oxygen plasma cleaning capabilities. Two studies are reported, each involving a comparison of the ECR in vacuum and nitrogen environments for measurements performed immediately after cleaning. The first study reports measurements of initial resistance (resistance measured upon first time closure) versus pressure as dodecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Electrically conductive stable oxides could also be considered as prospective NEM switch contact materials, as they have shown reliable performance for microscale contacts. For example, switches based on ruthenium oxide RuO 2 –Au contacts [ 149 , 151 152 ] reached more than 10 10 switching cycles without failure, surpassing such materials combinations as Pt–Au and Ir–Au [ 149 ]. As RuO 2 has lower surface reactivity than, for example, Pt, the RuO 2 –Au contact material combination prevents cycling-induced tribopolymer accumulation [ 149 ].…”
Section: Reviewmentioning
confidence: 99%
“…Electrically conductive stable oxides could also be considered as prospective NEM switch contact materials, as they have shown reliable performance for microscale contacts. For example, switches based on ruthenium oxide RuO 2 –Au contacts [ 149 , 151 152 ] reached more than 10 10 switching cycles without failure, surpassing such materials combinations as Pt–Au and Ir–Au [ 149 ]. As RuO 2 has lower surface reactivity than, for example, Pt, the RuO 2 –Au contact material combination prevents cycling-induced tribopolymer accumulation [ 149 ].…”
Section: Reviewmentioning
confidence: 99%
“…To address these challenges, solutions have been proposed to improve permanent contacts between graphene and electrode materials by e-beam nano-welding [ 21 ], or incorporating adhesion layers or changing the contact geometries [ 22 ]. However, in the case of dynamic or periodically actuated electrical contacts, which are essential for devices such as microelectromechanical systems (MEMS), controlling electrical current flow in the contact zone is not a straightforward procedure, even for well-studied noble metal interfaces [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that corrosion product due to the surrounding environment, such as atmospheric corrosion, temperature, humidity, dust contamination [7][8][9][10], has long been known as one of the major degradation mechanisms for electrical contacts, which will cause high contact resistance and even poor reliability of electric system. Contact failure caused by corrosion shows that the corrosion behavior of connectors should be taken under consideration, especially for the devices used in field environments [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%